Pengaruh WCTO Terhadap CR pada Perusahaan Sektor Pertambangan yang Terdaftar di BEI - Tri Yuniarti; Hasbi Assidiki Mauluddi; Rosma Pakpahan (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This research of aimed to understand the influence of working capital turnover to current ratio of mining company. The population are all mining companies listed on the Indonesia Stock Exchange (BEI) in 2008-2012. There are 5 companies selected using purposive sampling method. This research method use panel data regression with eviews9. The selected panel data regression method is Common Effect Model The result shows that Working Capital Turnover have significant effect on Current Ratio.